Hospital acquired malnutrition in orally fed geriatric patients: what’s the role of a hospital dietetics and food service? - ORLANDONI, PAOLO; JUKIC PELADIC, NIKOLINA; COLA, CLAUDIA; VENTURINI, CLAUDIA; COSTANTINI, ANNARITA; GIORGINI, NATASCIA; BASILE, REDENTA; SPARVOLI, DEBORA; DAVID, SERENELLA (Progress in Nutrition, 2018)
Background: The malnutrition delays recovery from illness and prolongs the hospitalization and its costs. It frequently occurs during hospitalization because of the low intake of patients. The aim of the study was to identify the key barriers to adequate dietary intake of geriatric patients. Methods: A two day survey among hospital in-patients of an Italian geriatric hospital - INRCA (Ancona) – was performed in October 2015. Two structured questionnaires were used to collect data on clinical, functional and nutritional status of 75 orally fed patients (84.5±6.9 years) as well as on their intake, food preferences and reasons for non eating. The Harris-Benedict formula corrected for age, disease and physical activity was used to assess patients’ energy needs, a reference range from 1.0 to 1.5 g of proteins/body weight to assess their protein needs. Nutritional values of food served were compared to values of food consumed and patients’ needs. Patients’ preferences and reasons for non eating were analyzed. Results: Three main diets were found: standard diet, diet for dysphagia and low glycemic diet. Discordance between food provided, patients’ needs and their intake was found for all diets and, in particular, for the diet for dysphagia. Very low intakes were registered. Patients’ preferences were focused on first courses, primary pasta and soups and on homogenized fruit. Insufficient assistance during meals was the most common reason for not consuming everything offered. Conclusions: Hospital dietetics and the organization of the food provision service for geriatric patients should better match both patients’ preferences and their impairments.